2014
DOI: 10.9790/487x-1561427
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Asymmetric Information, Transaction Cost To Corporate Governance, And Public Organization Performance (Study In Local Water Company In Malang Regency)

Abstract: Governing government sector is not quite different with managing a company. When the purpose of private sector is to corporate stability and long-lasting profit ability, in fact the purpose of public sector is not much different. The purpose of public sector is to improve community welfare and community trust to government. Welfare itself could be accomplished if the implementation of the development program itself gives positive impact for the society. (Sifia from Aswanto, 2010) When regional autonomy law is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…Tesco supermarket huge loss was a serious issue which would have made Tesco supermarket bankrupt, but the chief executive officer was able to recognize transaction cost theory. Priyanto et al (2014) found out that transaction costs have an indirect influence towards organization performance, positive business performance influence in an organization. Transaction costs analysis can play a significant act of seeing into a situation on possible beginning stages of intervention policy (Ostertag 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tesco supermarket huge loss was a serious issue which would have made Tesco supermarket bankrupt, but the chief executive officer was able to recognize transaction cost theory. Priyanto et al (2014) found out that transaction costs have an indirect influence towards organization performance, positive business performance influence in an organization. Transaction costs analysis can play a significant act of seeing into a situation on possible beginning stages of intervention policy (Ostertag 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Husmann (2015) noted that high transaction costs are the cause of market failure, in other words, poor business performance. Priyanto et al (2014) argue that outrageous transaction costs will lead to increasing the selling price of the product, which will be a financial responsibility to the consumer. Similarly, Petrović and Krstić (2011) emphasized that the conspicuous of the imperfect functioning of the market is due to a high level of transaction costs, which has a straight consequence on business organization performance as well as efficient operations of the economic.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Information is unequal among transaction parties i.e. one party has more information than the other (Bwalya, 2013;Priyanto et al, 2014). The partner who has less information fails to make rational decision due to lack of knowledge about the circumstances (bounded rationality).…”
Section: H5 Opportunism Of Exchange Partners Positively Relate To Thementioning
confidence: 99%
“…These informal and personal connections do not have formal and written agreement but these connections are based on network relationships with family members, relatives, friends, exchange partners, supportive institutions and the others (Bhagavatula, 2009;Lu, 2007;Priyanath and Premaratne, 2017). Literature describes that the network structure facilitates access to information (Adler and Kwon, 2002;Burt, 1992;Granovetter, 1983) and has an ability to access information reducing information asymmetric (Bwalya et al, 2013;Priyanto et al, 2014). Network structure helps SEs to mitigate information asymmetric facilitating to access information which enable to improve rational ability and mitigate the opportunism of exchange partners (Henningsen and Henning, 2013;Richman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The key benefit of SC is that it facilitates the reach of information and increases the quality and relevance of information (Adler & Kwon, 2002;Burt, 1992;Granovetter, 1983). Thus, SC facilitates the access of information reducing information asymmetry (Bwalya, Mugisha, & Hyuha, 2013;Priyanto, Mazkie, & Khusaini, 2014) and helps SEs to mitigate information asymmetry enabling the access of information leading to the mitigation of the opportunism of exchange partners (Henningsen & Henning, 2013;Richman, 2006).…”
Section: Introductionmentioning
confidence: 99%